2019
DOI: 10.1016/j.heliyon.2019.e02387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gabapentin on fetal rat brain and its amelioration by ginger

Abstract: Intrauterine exposure to antiepileptic drugs (AEDs) is associated with neurodevelopmental alterations causing postnatal behavioral and cognitive alterations. These disorders are associated with the interference of these AEDs with the developing cerebral cortex and hippocampal neurons. Therefore, it is crucial to identify the drugs that should be avoided during pregnancy in order to prevent AED mediated developmental alterations. The present study was conducted to investigate the effects of prenatal exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…Moreover, the biochemical investigation showed improvement in the levels of oxidative stress markers and in ammatory marker (TNF-α) levels. This is consistent with Badawy et al [19] study that con rmed the protection of ginger against the neurochemical and histopathological damage of brain and CNS tissues induced by the antiepileptic drug, gabapentin. Furthermore, El-Akabawy and El-Kholy [61] showed that ginger reduced the inducible levels of TNF-α, GFAP, and AChE in diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the biochemical investigation showed improvement in the levels of oxidative stress markers and in ammatory marker (TNF-α) levels. This is consistent with Badawy et al [19] study that con rmed the protection of ginger against the neurochemical and histopathological damage of brain and CNS tissues induced by the antiepileptic drug, gabapentin. Furthermore, El-Akabawy and El-Kholy [61] showed that ginger reduced the inducible levels of TNF-α, GFAP, and AChE in diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
“…In neurons, Bax is thought to be the main executioner and plays an essential role in neuronal cell death in processes as diverse as developmental apoptosis, hypoxia, ischemia, oxidative stress, nerve growth factor withdrawal, and nerve injury ( [57]. It was postulated that neuronal apoptosis represents one of the mechanisms causing side effects of antiepileptic drugs [19]. In the present study, the brain of Topamax® treated animals showed strong Bax protein expression.…”
Section: Discussionsupporting
confidence: 48%
“…Purkinje cells play a crucial role in motor coordination and alteration in structure or functions of these cells may cause changes in motor coordination function [23,24]. There has been some evidence of cerebellar dysfunction in pregabalin intoxication in the form of nystagmus, in-coordination, myoclonus and ataxia [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also showed that a dose of 2000 mg/kg in females significantly reduced the number of live fetuses and increased fetal death and resorption, but no adverse effects were observed for the doses of 250 and 500 mg/kg. The daily administration of ginger extract (at a dose of 200 mg/kg bw) to pregnant rats during the organogenesis phase of gestation, i.e., from 6th to 15th day of gestation, 1 h after gabapentin injection, minimized the brain damage in rat fetuses caused by this antiepileptic drug [ 77 ]. In addition, the immuno-histochemical investigation found that co-administration of ginger after gabapentin injection resulted in a significant decrease in the expression of the pro-apoptotic marker Caspase-3 and an increase in the expression of the anti-apoptotic marker Bcl-2 in fetal rat brains.…”
Section: Herbal Medicines Used To Counteract Some Pregnancy-related Symptoms (Eg Nausea and Vomiting Dizziness And Headache And Memory Lomentioning
confidence: 99%